Application of metal nanoparticle–hydrogel composites in tissue regeneration - Tan, Hui Li; Teow, Sin Yeang *; Pushpamalar, Janarthanan (MDPI, 2019)
Challenges in organ transplantation such as high organ demand and biocompatibility issues have led scientists in the field of tissue engineering and regenerative medicine to work on the use of scaffolds as an alternative to transplantation. Among different types of scaffolds, polymeric hydrogel scaffolds have received considerable attention because of their biocompatibility and structural similarity to native tissues. However, hydrogel scaffolds have several limitations, such as weak mechanical property and a lack of bioactive property. On the other hand, noble metal particles, particularly gold (Au) and silver (Ag) nanoparticles (NPs), can be incorporated into the hydrogel matrix to form NP–hydrogel composite scaffolds with enhanced physical and biological properties. This review aims to highlight the potential of these hybrid materials in tissue engineering applications. Additionally, the main approaches that have been used for the synthesis of NP–hydrogel composites and the possible limitations and challenges associated with the application of these materials are discussed